Beliefs and Practices towards Teaching and Learning Grammar: A Multicase Study - Patrícia Ferreira (Universitat Autònoma de Barcelona, 2014)
This text presents a multi-case study focused on 5th and 6th grades’ (10 - 12 years-old students) teachers’ beliefs and practices towards the process of teaching and learning grammar. Current practices of grammar instruction are connected to prescriptive approaches, outdated, disconnected from linguistic theory, and ineffective at improving communicative skills. Research has revealed that to promote real changes in practices it is important to act upon all the dimensions of teachers’ professional knowledge, including tacit phenomena, like beliefs, by means of professional training and development. The recent modification of the Portuguese Language curriculum reflects a new paradigm in grammar teaching, based upon a constructivist approach. Therefore, it is relevant to know how teachers implement it and how what they think about teaching grammar affects their practices.Data analysis revealed inconsistencies between beliefs and practices, leading to the conclusion that teachers have difficulties facing the required adjustment to the emerging paradigm.